Preparation, structure and activity of polysaccharide phosphate esters - Shiyang Zhou (Elsevier, 2021)
Polysaccharides have anti-virus, anti-cancer, anti-oxidation, immune regulation, hypoglycemia and other biological activities. Because of their safety, fewer side effects and other advantages, polysaccharides are considered as ideal raw materials in food and drugs. The biological activity of polysaccharides can be improved by structural modification (such as sulfation, carboxymethylation, phosphorylation, etc.), and even new biological activity can be generated. In this review, the recent advances in the phosphorylation of polysaccharides were reviewed from the perspectives of modification methods, structures, biological activities and structure-activity relationships.